(untitled) (Texas Journal of Engineering and Technology, 2022)
Modern construction practice involves the widespread use of chemical additives in concrete. As a chemical additive, there is not a kind of effective, universal and easy-to-use tool for radically changing the properties of concrete mixture and concrete.